The Figure of Moses in Jubilees - Ḳugel, G'aims 1945- (2012)
Moses is a central figure in numerous Second Temple period writings: in a number of them, he is even presented as a semi-divine »God-like man.« By comparison, the Moses of the book of Jubilees is a rather pale figure, altogether overshadowed by the towering portraits of Noah, Abraham, Jacob, and others. The reason for this calculated de-emphasis of Moses' importance and role is connected to the contrasting ideologies of two writers, the original author of Jubilees and an interpolator responsible for some 29 insertions into the original author's text.